Glutathione exposes sequential IgE‐epitopes in ovomucoid relevant in persistent egg allergy. Issue 3 (24th January 2013) - Roth‐Walter, Franziska; Starkl, Philipp; Zuberbier, Torsten; Hummel, Karin; Nöbauer, Karin; Razzazi‐Fazeli, Ebrahim; Brunner, Richard; Pali‐Schöll, Isabella; Kinkel, Janis; Felix, Ferdinand; Jensen‐Jarolim, Erika; Kinaciyan, Tamar
<x xml:space="preserve">Abstract</x> Scope Patients with persistent egg allergy have more immunoglobulin E (IgE) against sequential than conformational epitopes of ovomucoid (OVO). Here, we aimed to identify compounds capable to render sequential epitopes in egg. Methods and results Glutathione was used for in vitro reduction of OVO and circular dichroism analyses were performed. Glutathione reduced OVO in a concentration‐dependent manner. Egg white was analyzed for reduced proteins with a thiol probe and by MALDI‐TOF/TOF. In unprocessed total egg white, several reduced proteins were detected by the thiol probe, among them reduced ovalbumin could be confirmed with MS analyses. Egg‐allergics or sensitized controls were tested serologically (n = 19) for IgE against native and reduced OVO and in skin prick tests (n = 9). More patients had IgE against reduced than native OVO in Western blots. In skin prick test, five out of seven persistent egg‐allergics and none of the controls reacted with reduced OVO. Conclusion Reduced egg proteins are present in natural egg white. Glutathione, which is present in egg and furthermore is used as texture‐improving additive in processed food, is capable of reducing OVO. Patients with persistent egg allergy reacted rather to reduce the native OVO. Hence, our data indicate that reduction is a novel natural and processing‐associated principle, which contributes to the allergenicity of food.